Lawyers and the public good : democracy in action? - Paterson, Alan. (Cambridge, UK : Cambridge University Press, 2012)
Chiefly covers Great Britain, but also includes some discussion of several other common law jurisdictions.
Includes bibliographical references (p. 198-211) and index.
Keywords: Public interest law -- United Kingdom; Lawyers -- United Kingdom; Judges -- United Kingdom; Justice, Administration of -- United Kingdom; Democracy -- United Kingdom